Pengaruh Self Efficacy, Work Engagement, dan Job Satisfaction terhadap Organizational Citizenship Behavior di Perusahaan Manufaktur - Kannia Rinjani Putri Zahra; Gilang Pratama Hafidz (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2026)
This study is based on the importance of employees' voluntary work behavior in supporting organizational effectiveness, particularly in manufacturing companies that have high productivity and work quality demands. The phenomenon of low employee involvement and extra contributions outside of formal duties encourages the need for a study of the psychological factors and work attitudes that influence it. This study aims to analyze the influence of self-efficacy, work engagement, and job satisfaction on organizational citizenship behavior in manufacturing companies. This study uses a quantitative approach. Data were obtained by distributing questionnaires to 120 employees who had worked for at least one year, using purposive sampling. The results show that self-efficacy has a positive and significant effect on work engagement and job satisfaction, indicating that employees' belief in their abilities can increase work engagement and satisfaction. Furthermore, work engagement has a positive and significant effect on job satisfaction, but does not have a significant effect on organizational citizenship behavior. In addition, job satisfaction has been proven to have a positive and significant effect on organizational citizenship behavior, which shows that job satisfaction plays an important role in encouraging voluntary work behavior among employees. This study has limitations because it only examines the variables of self-efficacy, work engagement, job satisfaction, and organizational citizenship behavior within a limited scope of companies and regions. Further research is recommended to add other variables or mediating variables and expand the object and industrial sector in order to obtain more representative results with broader generalizability.